Examining fear of cancer recurrence in primary brain tumor patients and their caregivers using the Actor‐Partner Interdependence Model. Issue 7 (9th March 2021) - Braun, Sarah Ellen; Aslanzadeh, Farah J; Thacker, Leroy; Loughan, Ashlee R
Abstract: Objective: Fear of cancer recurrence (FCR) is related to psychological distress and poor quality of life in cancer patients and their caregivers. However, no studies have investigated FCR in neuro‐oncology. Given the varied prognosis, treatment, and disease trajectory of brain cancer, FCR may affect patients and their caregivers differently. Methods: Eighty adult primary brain tumor (PBT) patients and 52 caregivers completed questionnaires assessing FCR and psychological distress (depressive symptoms, generalized anxiety, and death anxiety). Differences in patient and caregiver FCR by demographic and medical characteristics were examined. Using multilevel modeling, the Actor‐Partner Interdependence Model (APIM) was used to investigate the interrelationship between patient and caregiver FCR with demographics and psychological distress measures. Results: Caregivers reported significantly higher FCR than patients. There were no effects of demographic or medical characteristics on patient FCR. Time since diagnosis was negatively related to caregiver FCR. All measures of psychological distress exerted a significant actor effect on FCR among both patients and caregivers. Two partner effects were found: caregiver depressive symptoms and death anxiety negatively predicted patients' FCR. Conclusions: This is the first investigation of FCR in PBT patients and their caregivers. Most demographic and medical characteristics were not related to patient or caregiver FCR. Caregiver FCR may be higher at the time of diagnosis and decrease over time. APIMs revealed actor effects on patient and caregiver FCR for all measures of psychological distress. Results demonstrated the dyadic effects of a brain tumor diagnosis, emphasizing the need to include caregivers in psychotherapy for neuro‐oncology patients.